Research and development in intelligent systems XXVIII incorporating applications and innovations in intelligent systems XIX : proceedings of AI-2011, the thirty-first SGAI international conference on innovative techniques and applications of artificial intelligence - SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence 2011 Cambridge, England); Bramer, Max.; Petridis, Miltos; Nolle, Lars.; SpringerLink (Online service). (London Springer, 2011)
The papers in this volume are the refereed papers presented at AI-2011, the Thirty-first SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence, held in Cambridge in December 2011 in both the technical and the application streams. They present new and innovative developments and applications, divided into technical stream sections on Planning, Evolutionary Algorithms, Speech and Vision, and Machine Learning, followed by application stream sections on Knowledge Discovery and Data Mining, Machine Learning and AI in Action. The volume also includes the text of short papers presented as posters at the conference. This is the twenty-eighth volume in the Research and Development in Intelligent Systems series, which also incorporates the nineteenth volume in the Applications and Innovations in Intelligent Systems series. These series are essential reading for those who wish to keep up to date with developments in this important field.
Random Prism: An Alternative to Random Forests -- Exploiting Automatic Validation in Human Mission Planning -- Real-Time Path Planning using a Simulation-Based Markov Decision Process -- Plan Graph with Interaction Estimates for Probabilistic Planning -- A Hybrid Parallel Genetic Algorithm for the Winner Determination Problem in Combinatorial Auctions -- Validation Sets, Genetic Programming and Generalisation -- A Hyper-Heuristic Approach to Evolving Algorithms for Bandwidth Reduction Based on Genetic Programming -- Two stage speaker verification using Self Organising Map and Multilayer Perceptron Neural Network.-Investigation into Computer vision methods to extract information for Context based image retrieval methods -- A Multimodal Biometric Fusion Approach based on Binary Particle Optimization -- Using Negation and Phrases in Inducing Rules for Text Classification -- Choosing a Case Base Maintenance Algorithm using a Meta-Case Base -- Successive Reduction of Arms in Multi-Armed Bandits -- 2D Mass-spring-like Model for Prediction of a Sponge`s Behaviour upon Robotic Interaction -- Quality Management Using Electrical Capacitance Tomography and Genetic Programming: A new Framework -- MOEA/D with DE and PSO: MOEA/D-DE+PSO -- Cross Organisational Compatible Plans Generation Framework -- A Neural Network for Counter-Terrorism S. Dixon, M. Dixon, J. Elliott, E. Guest and D. Mullier (Leeds Metropolitan University, UK) -- Web Community Knowledge Extraction for myCBR 3 -- Web-Site Boundary Detection Using Incremental Random Walk Clustering -- Trend Mining and Visualisation in Social Networks -- DenGraph-HO: Density-based Hierarchical Community Detection for Explorative Visual Network Analysis -- Using the Gamma Test in the Analysis of Classification Models for Time-Series Events in Urodynamics Investigations -- DScentTrail: A New Way of Viewing Deception -- Semi-Automatic Analysis of Traditional Media with Machine Learning -- Design of Robust Space Trajectories -- Intelligent Tuning of a Dynamic Business Simulation Environment -- Towards Large-Scale Multi-Agent Based Rodent Simulation: The Mice In A Box Scenario -- Analysis of IDDM Rats.
Electronic reproduction.
Keywords: Artificial intelligence -- Congresses; Computer science; Electronic books